Topographical survey engineering education retrofitted by computer-aided 3D-printing - Wang, Chen; Yap, Jeffrey Boon Hui; Li, Heng; Chua, Jiayun; Abdul-Razak, Asrul Sani; Mohd-Rahim, Faizul Azli (John Wiley & Sons, 2018)
Due to the sophisticated nature of contour lines on 2D drawings, students often find difficulties in visualizing three-dimensional interpretations of flat and 2D displays, especially when they attempt to comprehend topographic maps. This study aims to determine the issues encountered in topographical survey education that could be mitigated by 3D-printed models and to explore the effectiveness of hands-on 3D-printing exercises in real teaching practices by guiding students to design and fabricate 3D models using 3D-printing techniques. A mixed method combining quantitative and qualitative approaches has been employed including experiments and structured interview surveys. The qualitative ethnographic method through a qualitative experiment developed 3D-printed models for topographic education. Topographic maps were developed using Sketchup Version 8 software in order to fabricate the 3D topographic models. Hands-on 3D-printing exercises engender better understanding and appreciation of topographic maps among the students. This research demonstrates how 3D models could complement the conventional teaching using 2D maps in university education.